IMPLEMENTASI KEBIJAKAN PENANGGULANGAN PENYAKIT TUBERKULOSIS DI PUSKESMAS KAMONJI KOTA PALU - Abraham, Royke (Katalogis, 2018)
This research aims to find out the implementation of tuberculosis disease control policy at Kamonji Public Health Center in Palu City. The analysis used Edward III implementation theory with inductive descriptive research method and 6 informants determined purposively. The data were collected through observation, interview, and documentation. The research result show that implementation of tuberculosis disease pervention policy has not been effective because the factor of communication was the lack of information dissemination of tuberculosis disease management on officers and communities that were not consistently implemented and method that did not yet appropriate. Aspects of bureaucratic structures were cross program officers which unsupported the discovery of tuberculosis sufferer. The resource factor of officer and financing are sufficient and disposition that is the attitude of the implementer have shown support for the implementation of policy of tuberculosis disease preventation.